2020
DOI: 10.1530/ec-20-0074
|View full text |Cite
|
Sign up to set email alerts
|

MODY2 in Asia: analysis of GCK mutations and clinical characteristics

Abstract: Aims Heterozygous inactivating mutations in the GCK gene cause the familial, mild fasting hyperglycaemia named MODY2. Many patients with MODY2 in Asia have delayed timely treatment because they did not receive the correct diagnosis. This study aims to analyze the clinical characteristics and GCK mutations in Asian MODY2. Methods We have collected 110 Asian patients with MODY2 from the PubMed, Embase, Medline, Web of Science, CNKI, and Wanfang with the following search terms: ‘maturity-onset diabetes of the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Indeed, the c.571C>T mutation has been previously identified in individuals (pregnant women, children and adolescent) with MODY2 phenotype of British ( 46 ), Italian ( 47 ), Korean ( 48 ), Belgian ( 49 ), Norwegian ( 50 ), French ( 51 ), Japanese ( 52 ), Brazilian ( 53 ), Chinese ( 45 ) and Tunisian ( 20 ) descent. HGMD Professional has also reported three other amino acid substitutions on the same residue (p.Arg191Leu/Gln/Glu) related to MODY2 ( 47 , 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the c.571C>T mutation has been previously identified in individuals (pregnant women, children and adolescent) with MODY2 phenotype of British ( 46 ), Italian ( 47 ), Korean ( 48 ), Belgian ( 49 ), Norwegian ( 50 ), French ( 51 ), Japanese ( 52 ), Brazilian ( 53 ), Chinese ( 45 ) and Tunisian ( 20 ) descent. HGMD Professional has also reported three other amino acid substitutions on the same residue (p.Arg191Leu/Gln/Glu) related to MODY2 ( 47 , 54 , 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…HbA1c is usually 5.6-7.6%, and fasting glucose is always 5.5-8.5 mmol/L. 75.8% of patients had a level of 2h-postprandial blood sugar below 11.1 mmol/L, and the increments of blood glucose were 2.82 ± 2.03 mmol/L during OGTT (20). Multiple studies showed MODY 2 patients do not require antihyperglycemic medication except during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…The c.574C>T (p.R192W) mutation was located in exon 5 and the other two were located in exon 7. Exons 5 and 7 were common mutation sites in 110 Asian patients with GCK-MODY based on a literature search in PubMed, Embase, MEDLINE, Web of Science, CNKI, and Wanfang ( Zhou et al, 2020 ), suggesting that the hotspot mutation sites of GCK in Asian patients might be located in exons 5 and 7, whereas the hotspot mutation sites of GCK in Europe patients might be located in exons 7 and 10 ( Pruhova et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%